Turning the World Upside Down: Playing as the Deliberate Creation of Uncertainty - Stuart Lester; Wendy Russell (MDPI AG, 2014)
Risk is big business. It has assumed almost universal acceptance as an ever-present reality of life, something out there waiting to cause harm (most notably to political, economic and health systems). It commands vast resources to develop preventative measures that are the preserve of experts issuing often contradictory advice and warnings. Children's play is caught up in this account. No longer something that children just do, it is subject to adult scrutiny that simultaneously and paradoxically attempts to manage risk and promote "risk-taking" for its perceived instrumental benefits, primarily the development of risk assessing skills. Adults thus guide children's play, rendering children passive and needy recipients of expertise. This article takes a broader perspective to consider how this contemporary understanding of risk plays out in material discursive practices in relation to childhood, play, health and wellbeing. It then draws on conceptual tools of relationality, materiality and performativity to reconfigure playing as an emergent co-production of entangled bodies, affects, objects, space and histories in ways that make life better for the time of playing. Such moments produce health-affirming potential as an intra-dependent phenomenon rather than an individual achievement. Finally, it considers implications for "health promotion" and health enabling environments.